2013
DOI: 10.1186/1297-9686-45-8
|View full text |Cite
|
Sign up to set email alerts
|

Survival, growth and sexual maturation in Atlantic salmon exposed to infectious pancreatic necrosis: a multi-variate mixture model approach

Abstract: BackgroundOutbreaks of infectious pancreatic necrosis (IPN) in Atlantic salmon can result in reduced growth rates in a fraction of the surviving fish (runts). Genetic and environmental variation also affects growth rates within different categories of healthy animals and runts, which complicates identification of runts. Mixture models are commonly used to identify the underlying structures in such data, and the aim of this study was to develop Bayesian mixture models for the genetic analysis of health status (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…We found a moderate significant genetic variation for early growth rate (0.30 ± 0.05). Similar heritability values have been reported for growth rate in others salmonid species, ranging from 0.32 to 0.35 (Lillehammer et al, 2013;Silverstein et al, 2009).…”
Section: Accepted Manuscript 20supporting
confidence: 84%
See 1 more Smart Citation
“…We found a moderate significant genetic variation for early growth rate (0.30 ± 0.05). Similar heritability values have been reported for growth rate in others salmonid species, ranging from 0.32 to 0.35 (Lillehammer et al, 2013;Silverstein et al, 2009).…”
Section: Accepted Manuscript 20supporting
confidence: 84%
“…Bivariate linear animal models were used to estimate the variance and covariance components among the traits (Lillehammer et al, 2013;Ødegård et al, 2014;Yáñez et al, 2016). Bivariate models were defined as follows:…”
Section: Discussionmentioning
confidence: 99%
“…Studies in other species pointed out that survivals in the early phase of development or during grow-out are lowly heritable such as in shrimp [ 6 ], freshwater fish (tilapia and common carp) [ 3 , 4 ] or abalone [ 22 ]. On the other hand, a number of studies also reported moderate heritability for survival under field grow-out conditions for Atlantic salmon [ 24 ] or another population of common carp [ 25 ] and tilapia [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Disease resistance used to be considered a difficult trait to improve by genetic selection based on low heritability estimates for some fish species (Gjedrem, 1985). But lately, numerous studies have reported moderate to high heritability for disease resistance and/or survival in fish species due to improvements in challenge techniques (Gjerde et al, 2009;Henryon et al, 2005;Johnson et al, 2007;Lillehammer et al, 2013;Ødegård et al, 2007;Taylor et al, 2009), indicating that selective breeding to enhance disease resistance can be successful. In contrast, such estimates for disease resistance are absent for oyster species except for OsHV-1 lvar resistance in Crassostrea gigas (Dégremont et al, 2015a,b).…”
Section: Introductionmentioning
confidence: 99%